Respostas fisiológicas e eletrencefalográficas ao exercício físico agudo e máximo em indivíduos com epilepsia - Vancini, Rodrigo Luiz [UNIFESP] (2010)
Introduction: Epilepsy is the most common chronic neurological disorder in the world. In addition to drug treatment and surgery, complementary treatments have been studied, such as physical exercise. Despite important advances in understanding the effects of an exercise program in experimental models of epilepsy, little is known about these effects in humans, probably by the practical limitations encountered in conducting research in people with epilepsy. Whereas people with epilepsy are mostly sedentary, cardiorespiratory fitness of these people may be impaired when compared to healthy pairs of the same age, gender and status of training. Additionally, the evaluation of electroencephalographic responses by electroencephalogram (EEG) during intense physical effort in persons with epilepsy has been little explored. The analysis of behavior of physiological variables and EEG at rest, during cardiopulmonary exercise test (CPET) and in the recovery period may reveal peculiarities in people with epilepsy that may be useful in therapeutic procedures. Objetives: To evaluate the physiological responses and EEG in the resting state, during the CPET and in the recovery after CPET of people with epilepsy, comparing them with those of healthy people. Casuistic e Methods: We evaluated 40 persons of both sexes matched by gender, body mass, age and status of training, of which 20 composed the epilepsy group (EG) and 20 the control group (CG). The following assessments and measurements were conducted: level of habitual physical activity, quality of life, CPET, EEG and heart rate variability. Results: The level of physical activity performed during leisure time was 14.4% higher in CG compared to EG. In the evaluation of quality of life, were found values significantly lowers in the EG for the emotional well-being (18%), cognitive function (31.5%) and global health status (27%) compared to CG. With respect to physiological responses obtained from CPET only the values of V . O2peak (16.2%), V . O2 anaerobic threshold (18.5%) and V . O2 from the point of respiratory compensation (16%) were significantly lowers in EG compared to the CG. These findings may be related to lower levels of physical activity performed during leisure time at the EG. Although the EEG findings were not statistically significant, it was observed a reduced number of epileptiform discharges in the EG from resting state to physical effort (82%) and from resting state to the recovery period (74%). Moreover, after discontinuation of CPET the number of epileptiform discharges increased again by approximately 30%. The indexes which measure the heart rate variability, in the time and frequency domains, were not different between the groups in the resting state, during CPET and recovery after the test. Conclusions: People with epilepsy present lower aerobic fitness than the general population. This fact seems to be associated with sedentary habits. Moreover, the practice of vigorous exercise seems to have a beneficial effect for people with epilepsy, characterized by a reduction in epileptiform discharges in the phases of exercise and recovery compared with the resting condition. It seems that there are no peculiarities in the physiological responses during incremental exercise that required a differential care in assessing the aerobic fitness of these people.